Lifelong learning and the Roma minority in western and southern Europe - Óhidy, Andrea; Forray, Katalin R. (Emerald Publishing Limited, 2019)
The achievement and success of Roma people in education is at a breaking point across Europe, severely limiting social mobility. Recent research has shown that Roma are the most underrepresented group in schools and other educational institutions. There are an array of policy measures and initiatives across Western and Southern Europe seeking to reverse this and to raise educational access and attainment of the Roma population.This book offers an in-depth exploration into the current educational climate and the impact of these policy measures for Roma people in seven Western and Southern European countries: Germany, Greece, Italy, Norway, Portugal, Spain and Sweden. This book seeks to raise awareness of this forgotten minority and to assess the policies implemented to integrate the Roma people into the education system. Written by experts across Western and Southern Europe and drawing on varied cultural perspectives, this work will help to address the severe lack of information and knowledge about the Roma people available in the public domain. This book will prove invaluable to those in the field of comparative education, educational leaders and practitioners in Western and Southern Europe and beyond.